Peningkatan Hasil Belajar Siswa Kelas 6 pada Materi Bumi dalam Bahaya melalui Video Ajar dengan Model Discovery Learning di SDN Gayam 1 - Siti Yuliana; Kharisma Eka Putri; Novi Rohmawati (Universitas Nusantara PGRI Kediri, 2025)
Education is one of the important elements to form the quality of human resources. Education is a demand that given to children in order to find all the natural strengths that children have so that children are able to achieve the highest safety and happiness both as humans and members of society. Based on the results of observations on grade 6 students of SDN Gayam 1, it can be seen that there are several problems in the learning process. Through observation and interviews, it is known that ineffective learning can lead to poor learning outcomes. Through video teaching media in the Discovery Learning model, it is hoped that it can help students find existing problems and then compare them with their experiences. From improving learning through classroom action research that has been applied to improve the learning outcomes of grade 6 students on the material of the earth in danger through teaching videos with the Discovery Learning model of SDN Gayam 1, it can result in an increase in student activity so that there is also an increase in student learning outcomes. In cycle 1 there was an increase with the percentage of student learning outcomes completion being 64.1%. In cycle 2, the percentage of student learning outcomes completion was 85.5%. So, it can be concluded that the application of the Discovery Learning model using video teaching media can improve the activeness and learning outcomes of grade 6 students at SDN Gayam 1.